Rodentolepis straminea (Cestoda: Hymenolepididae) in an urban population of Apodemus sylvaticus in the UK. Issue 4 (17th August 2015) - Rushworth, R.L.; Boufana, B.; Hall, J.L.; Brannan, V.; Mastin, A.; Birtles, R.J.; Craig, P.S.; Rogan, M.T.
Abstract: The presence of the cyclophyllidean cestode Rodentolepis straminea (Cestoda: Hymenolepididae), was confirmed by molecular DNA analysis from a wood mouse ( Apodemus sylvaticus ) population inhabiting urban woodland in Salford, Greater Manchester (UK) with a prevalence of 27.8%. It would appear that the only previously published record of this species in A. sylvaticus in the British Isles is that from south-west Ireland, where 24% of the wood mice examined were infected with R. straminea. This species has been recorded in studies on A. sylvaticus in continental Europe. The current report represents a new record for R. straminea on mainland Britain and a first study of helminth parasites in an urban wood mouse population.